THE IMPORTANCE OF ELECTRONIC LEARNING RESOURCES IN ORGANIZING AND CONDUCTING DISTANCE LESSONS. - Bakhromov Mansur Maksud oglu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article organizes distance education and gives students the opportunity to work independently on mastering the studied material. Taking into account the experience of students in the development of a distance lesson and using a modern type of ETR.